ASSESSMENT OF POTENTIAL DANGER OF HYDROEKOSYSTEM BOTTOM SEDIMENTS WITH INTENSIVE MAN MADE LOAD - Маджд, С. М.; Александрова, А. С. (Science-based technologies, 2016)
Bottom sediments are indicators of ecological water conditions by accumulated pollution that comes to water during long period of time and are spetial integral indicator of level and size of man made pollution. Because on the one hand they promote hidroekosystem self-cleaning and on the other hand they are constant source of water environment pollution. It is discovered that progressive hidroekosystem pollution is characterized by bottom accumulation coefficients growth while that coefficients decline means reducing pollution and detoxification processes activization. During research it is determined that bottom accumulation coefficients for hidroekosysten heavy metals and oil in zone of civil aviation enterprises influence point on bottom sediments potential danger. Bottom sediments pollutions accumulation means about intensive man made load on hidroecosystem fromaviation enterprises and progresove pollutants and accumulation most of the pollutants of aviation enterprises in bottom sediments.